Potentials of Miscanthus x giganteus for phytostabilization of trace element-contaminated soils: Ex situ experiment - Nsanganwimana, Florien; Al Souki, Karim Suhail; Waterlot, Christophe; Douay, Francis; Pelfrêne, Aurélie; Ridošková, Andrea; Louvel, Brice; Pourrut, Bertrand (Ecotoxicology and environmental safety, 2021)
Phytomanagement is proposed as a cost-effective and environmentally-friendly suggestion for sustainable use of large metal-contaminated areas. In the current work, the energy crop miscanthus (Miscanthus × giganteus) was grown in ex situ conditions on agricultural soils presenting a Cd, Pb and Zn contamination gradient. After 93 days of culture, shoot and root growth parameters were measured. Soils and plants were sampled as well to study the TE accumulation in miscanthus and the effects of this plant on TE mobility in soils. Results demonstrated that miscanthus growth depended more on the soils silt content rather than TE-contamination level. Moreover, soil organic carbon at T93 increased in the soils after miscanthus cultivation by 25.5-45.3%, whereas CaCl2-extractible TEs decreased due to complex rhizosphere processes driving plant mineral uptake, and organic carbon inputs into the rhizosphere. In the contaminated soils, miscanthus accumulated Cd, Pb and Zn mainly in roots (BCF in roots: Cd " Zn > Pb), while strongly reducing the transfer of these elements from soil to all organs and from roots to rhizomes, stems and leaves (average TFs: 0.01-0.06, 0.11-1.15 and 0.09-0.79 corresponding to Cd, Pb and Zn respectively). Therefore, miscanthus could be considered a TE-excluder, hence a potential candidate crop for coupling phytostabilization and biomass production on the studied Metaleurop TE-contaminated soils.
Keywords: biodegradace; listy rostlin; Biomass; Miscanthus; Soil Pollutants; Energy crop; Rhizosphere; látky znečišťující půdu; Plant Stems; rhizosféra; Plant Leaves; Phytostabilization; Poaceae; těžké kovy; lipnicovité; Biodegradation, Environmental; Excluder; biomasa; Metals, Heavy; stonky rostlin; Trace element mobility